Kasus “Sanding” antara Menantu Perempuan dengan Ibu Mertua yang Tinggal Serumah pada Masyarakat Batak Toba di Desa Situmeang Hasundutan Kecamatan Sipoholon Kabupaten Tapanuli Utara - Lenni E Situmeang; Jupalman W. Simbolon; Feriel Amelia Sembiring; Elvri T. Simbolon; Wensdy Sitindaon (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The case of young couples at the beginning of marriage still choose to live in the same house with their parents, especially from the husband's side, so that the wife is also required to follow her husband to live with his parents, in this case the in-laws for the wife, so that it can trigger household problems that encourage the in-laws to interfere in it. This study aims to determine the type of interpersonal conflict between daughters-in-law and mothers-in-law who live in the same house in the Batak Toba tribe in Situmeang Hasundutan Village, Sipoholon District and the causes of "sanding" between daughters-in-law and mothers-in-law who live in the same house in the Batak Toba tribe in Situmeang Hasundutan Village, Sipoholon District and How is the stereotype of society towards sanding between daughters-in-law and mothers-in-law who live in the same house in the Batak Toba tribe in Situmeang Hasundutan Village, Sipoholon District. This study uses a qualitative method with a descriptive approach. Data collection was conducted through direct interviews with informants; daughter-in-law, mother-in-law, husband, traditional leader, community. Descriptive analysis technique was conducted to analyze the “Case of “Sanding” Between Daughter-in-Law and Mother-in-Law Who Live in the Same House in the Batak Toba Community in Situmeang Hasundutan Village, Sipoholon District, North Tapanuli Regency”. The results of this study indicate that in the Batak Toba community in Situmeang Hasundutan Village, the conflict between daughter-in-law and mother-in-law is seen as a natural thing that is unavoidable, because there are several factors that occur, namely several types of conflicts that occur: Role conflict, Communication conflict, Cultural value conflict, Personality conflict. There are 2 Stereotypes of the Batak Toba community in Situmeang Hasundutan Village towards daughters-in-law who live in the same house with their mothers-in-law, namely positive stereotypes and negative stereotypes. Positive stereotypes: Role as a household manager, Guardian of customary values, Helping each other with household chores. Negative stereotypes: Intergenerational conflict, feelings of being pressured or unappreciated, lack of privacy.